Nickel and cobalt oxides based catalysts for the methanation reaction - Mohammad, Nurul Shafeeqa (2013)
The presence of acidic and toxic gases of carbon dioxide (CO2) and hydrogen sulphide (H2S) will lead to the corrosion in natural gas pipeline system and material in processing plant. Alternatively, CO2 and H2S can be removed using green technology via catalytic methanation reaction by converting CO2 to methane (CH4) gas. Nickel (Ni) and cobalt (Co) oxides are well known catalysts to exhibit higher activity however they are easily deactivated. It is essential to activate these catalysts by incorporating dopants to enhance the catalytic performance. So far, the alteration of these oxides catalysts by adding zirconium, cerium and samarium dopants did not boost up the activity. In this research, a series of alumina (Al2O3) supported Ni/Co oxides based catalysts doped with manganese (Mn) and noble metal oxides such as ruthenium (Ru) and palladium (Pd) were prepared by wetness impregnation method followed by calcination. Various parameters were studied in this research include compositions of catalyst, calcination temperatures, effect of H2S gas, different Mn precursors, effect of sonication, two series furnace testing, reproducibility and stability testing towards CO2/H2 methanation reaction. The catalysts were subjected to characterization process using various techniques such as XRD, FESEM-EDX, Nitrogen Adsorption, TGA-DTG and FTIR in order to study their physical properties. XRD diffractogram illustrated that the supported catalysts were in amorphous state at 1000°C calcination temperature and became crystalline at 1100°C. FESEM micrographs showed that both fresh and used catalysts have spherical shape with small particle sizes in agglomerated and aggregated mixtures. Elemental analysis performed by EDX confirmed the presence of Al, O, Ni, Co, Mn and Ru on the catalysts. Nitrogen Adsorption analysis revealed that both catalysts were in mesoporous structures with BET surface area in the range of 46-60 m2/g. The prepared catalysts were subjected to catalytic screening using micro reactor coupled with FTIR to study the performance of the catalysts by determining the percentage of CO2 conversion, meanwhile the percentage of CH4 formation was analyzed using GC. For nickel based catalyst, Ru/Mn/Ni(5:35:60)/Al2O3 calcined at 1000°C was found to be the potential catalyst which gave 99.74% of CO2 conversion and 72.4% of CH4 formation at the maximum reaction temperature of 400°C. This catalyst can be reused for seven recycles without treatment. Meanwhile, for cobalt oxide based catalyst, Ru/Mn/Co(5:40:55)/Al2O3 calcined at 1000°C was found to be the most potential catalyst which gave 96% of CO2 conversion at low reaction temperature of 250°C with 76% of CH4 formation. This catalyst can be reused for three recycles without treatment. In the presence of H2S, the CO2 conversion exhibited very low conversion to CH4 for both Ru/Mn/Ni(5:35:60)/Al2O3 and Ru/Mn/Co(5:40:55)/Al2O3 catalysts.